PENERAPAN TEORI KOGNITIF PIAGET DALAM PEMBELAJARAN DI SEKOLAH SEBAGAI DASAR MELAKSANAKAN REVOLUSI MENTAL - I Wayan Dana Ardika; AA. Raka Sitawati; Ni Ketut Suciani (Soshum: Jurnal Sosial dan Humaniora, 2014)
Education is essentially an interaction between educator (teacher) with learners (students) to achieve educational goals. This interaction is called the interaction of education, which is means a process of mutual influence between educators with learners in learning. According to Indonesia law no. 20 of 2003 explained that education is a conscious and deliberate effort to create an atmosphere of learning and the learning process so that learners are actively developing the potential for him to have a religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed him, society, nation, and the state. Education in general aim to help the students in developing themselves, namely the development of all the potential, skills, and personal characteristics of the positive direction, both for themselves and their environment. This research aims to know and understand about the dominant role of cognitive theory by Jean Piaget in the selection of an appropriate learning model. The problems discussed in this paper are: (1) how is the child's development according to Jean Piaget's cognitive dominant theory? (2) what kind of learning model suitable to be applied in the daily practice and their implications in the education system at school? Based on the result of discussion, it is known that according to the dominant cognitive theories by Jean Piaget, cognition evolved not because someone receives knowledge from outside the person passively but actively constructs the knowledge. The learning model is suitable to be applied by the dominant cognitive theory according to Piaget, a model of bottom-up or partnership. Such as quantum learning model, cooperative learning model, problem-based learning model, learning environment model, etc. To realize the whole process is a good thing with colaboration between learning model that is able to develop a whole person.